Outcome of Early Onset Systemic Lupus Erythmatosus - A Tertiary Care Study - Rafique, Iffat; Jamal, Yousaf; Saif, Mohsin; Rafeeq, Nuzhat; Ikram, Sana; Zaman, Adnan (Pakistan Armed Forces Medical Journal, 2025)
Objective: To evaluate the outcome of early onset systemic lupus erythematosus at tertiary care centre. Study Design: A cross sectional study. Place and Duration of Study: Combined Military Hospital, Kharian Pakistan, from Feb 2021 to Jan 2024. Methodology: Total 77 female patients both indoor and outdoor were included. Patients <16 years (juvenile onset) and >50 years (late onset lupus) were excluded. Clinical manifestations as fever, arthralgia, mucocutaneous lesions, malar rash, neuropsychiatric illness, and anaemias were observed on initial presentation. Outcome has been finalised by SPSS version 22. p-value of 0.05 or less was significant. Results: Total 77 individuals, all were women (100%), including 64(83.1%) housewives, and 13(16.9%) working ladies. Mean age of patients was 31.86%(±7.9 SD) between 18 to 48 years. Photosensitivity is observed in 64(83.1%) patients. Complications have been noticed in 46(59.8%) patients. 4(5.2 %) died of lupus nephritis. Flare of lupus seen in 24(31.2%) patients. Lupus cerebritis in 11(14.3%), pericarditis in 7(9.1%), and haemolytic anaemia in 4(5.2%) patients. 31(40.2%) patients went in remission. Conclusion: Early onset Systemic lupus Erythematosus has an aggressive clinical course. A substantial improvement in management, may help to improve the outcome and delay life-threatening complications.